The absent pulmonary valve syndrome - Bilgiç, Arman; Saraçlar, Muhsin; Özme, Şencan; Akçoral, Adnan; Aytaç, Aydın (The Turkish Journal of Pediatrics, 1982)
The clinical, radiological, electrocardiographic and hemodynamic findings in 9 patients with the absent pulmonary valve syndrome are reported, and the relation of this syndrome to tetralogy of Fallot is discussed.